Lexicalising clausal syntax the interaction of syntax, the lexicon and information structure in Hungarian - Laczkó, Tibor (Philologist) (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2021)
"The book presents a new perspective on clausal syntax and its interactions with lexical and discourse function information by analysing Hungarian sentences. It also demonstrates ways in which grammar engineering implementations can provide insights into how complex linguistic processes interact. It analyses the most important phenomena in the preverbal domain of Hungarian finite declarative and wh-clauses: sentence structure, operators, verbal modifiers, negation and copula constructions. Based on the results of earlier generative linguistic research, it presents the fundamental empirical generalisations and offers a comparative critical assessment of the most salient analyses in a variety of generative linguistic models from its own perspective. It argues for a lexical approach to the relevant phenomena and develops the first comprehensive analysis in the theoretical framework of Lexical-Functional Grammar. It also reports the successful implementation of crucial aspects of this analysis in the computational linguistic platform of the theory, Xerox Linguistic Environment"--